POWER AND PROPERTY: RETROSPECTIVE ANALYSIS OF CONSTRUCTION OF RELATIONS - Зайдель, М.І. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
It is examined the specific of relation building between authority and property and its determination by historical dynamics of social and political world model. Attention is paid to correlation of authority and property in precapitalist relations. Sources of formation the system of national states and primary capital accumulation should search for in feudalism and absolutism despite of interpenetration of authority and property in maximum.